eGovernment: the new frontier in governance - Misra, Dinesh Chandra (New Delhi, 2013)
This book provides an introduction to all basic concepts of eGovernment. The book also provides a specific roadmap to make India the No. 1 Internet Enabled Nation of the world.
Keywords: Internet in Public Administration